DIRECT RELATIONSHIP MANAGEMENT BETWEEN DENTISTS, THE PROMOTION SYSTEM AND THE DISTRIBUTION CHANNELS OF DENTISTRY PRODUCTS - BENDAS Ana-Maria; BURLEA Lucian Stefan; CHIHAI Jana; TUCMEANU Alin; CIUBARA Anamaria (Romanian Society of Oral Rehabilitation, 2019)
This project wreathes three years work in medical field and it comes to mark out and understand the main forces of marketing field followed by examples which underline the impact on the market of a distribution company and, also, understanding the company relationship between its internal and external environment, the direct relationship with the market and with its' the competitors. The aim of this cross-sectional study was to underline the relationship between the distibution companies and the private dental offices, also the direct relationship between the dentist and the promoting sistem, the distribution way of dentistry products. For a most acurate research, it's necessary to apply different methods of research in the market. The main methods are observation and investigation. The measurement of the products circulation in the final sale point- all across the distribution line-is the primary function of marketing research. In the study, measurements can be determinated by: the number of sold units, by the value in standard currency of total sales from one period to another. In relationship with the economic and social environment and also with the dentistry market, the marketing of modern companies can't limit only to the production process and distribution of the units; it involves a permanent and complex communication with the extern environment which imply a good information of the leaders, specific actions of lobby for sales and input; all those actions represents the promotion policy of the distibution companies of dentistry products